The Future of Work in the Twenty-First Century. Issue 1 (2nd January 2016) - Hodgson, Geoffrey M.
Abstract: The institutional nature of work has changed dramatically over the last three hundred years, and there is no reason to assume that change will cease in the twenty-first century. This article criticizes the theoretical basis for some previous confident predictions, including deskilling (Karl Marx), and massive reductions in the extent of the working day (John Maynard Keynes). I argue that further increases in the complexity and knowledge-intensity of work under capitalism are likely, although not inevitable. I consider some implications of growing complexity for work and the employment contract. Raising the question of possible asymmetries between labor and capital, I address their role in generating future increases in inequality. On the other hand, growing complexity may lead to radical changes in the employment contract and its evolution into a form of quasi-self-employment. But, in an increasingly knowledge-intensive system, those with inadequate training or skills may be left behind. Compensatory policy measures, such as a guaranteed basic income and wealth redistribution, remain on the agenda.